Flexural behavior of reinforced concrete beams strengthened with externally bonded Aluminum Alloy plates - Rasheed, Hayder A.; Abdalla, Jamal; Hawileh, Rami; Al-Tamimi, Adil K. (My University, 2017)
The objective of this experimental investigation is to study the viability and effectiveness of using Aluminum Alloy (AA) plates as externally bonded flexural reinforcement for reinforced concrete (RC) beams. Ten RC beams were prepared and nine of them were strengthened with externally bonded 2 mm and 3 mm thick AA plates with different mechanical properties. Four strengthened beams had no end wraps or anchorages. Single-layer and double-layer U-wrap CFRP sheets were used in the transverse direction as end anchorages for four strengthened beams and one beam had three double anchorages (two at the ends and one at mid-span). The beams were tested under monotonic load until failure. The goal is to study the effect of using AA plates as externally bonded flexural strengthening material and to explore the effect of end anchorages on the flexural strength and ductility of these beams. The increase in strength over the control unstrengthened specimen ranged from 13% to 40% while the ductility significantly surpassed that of beams strengthened with CFRP sheets. It is observed that the use of end anchorages enhanced the ductility but not the strength of the tested beams. It is also observed that beams without end anchorage failed predominantly in flexure with full de-bonding while beams with end anchorage failed by localized de-bonding and flexure. Furthermore, the performance of the tested beams was compared with numerical predictions by a computer program developed in this study. The results of the numerical models were in close agreement with the measured experimental data. It was concluded that AA plates could be used as an external strengthening material to enhance both the strength and ductility of RC beams in flexure.
Citation: Hayder A. Rasheed, Jamal Abdalla, Rami Hawileh, Adil K. Al-Tamimi, Flexural behavior of reinforced concrete beams strengthened with externally bonded Aluminum Alloy plates, Engineering Structures, Volume 147, 15 September 2017, Pages 473-485, ISSN 0141-0296, https://doi.org/10.1016/j.engstruct.2017.05.067.
Keywords: Aluminum Alloy plates; CFRP sheets; Flexural strengthening; Anchorage; Ductility enhancement